Analisis Motivasi Kerja Pegawai pada Kantor Kecamatan Tanah Kampung Kota Sungai Penuh - Nora Aprianti (Ebisma (Economics, Business, Management, & Accounting Journal), 2026)
This study aims to determine the motivation of employee work at Kecamatan Tanah Kampung office Kota Sungai Penuh. The Research methode research is qualitatif approach by doing interview method. The number of informants in this study is as many as nine people. Indicators for motivation variables based on Gibson opinions consisting of motives, expectations and incentives. Based on the result showed that the employee’s motivation is in good condition. Where this is contrary to the phenomenon that occuret Kecamatan Tanah Kampung office.